2003
DOI: 10.1074/jbc.m304370200
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia Induces Macrophage Cell Cycle Arrest by Adhesion-dependent Induction of p21Cip1 and Activation of the Retinoblastoma Protein

Abstract: Hyperoxia induces growth arrest, apoptosis, necrosis, and morphological changes (spreading and adhesion) in various types of cells. The mechanism of hyperoxia-induced cell growth arrest has not been well elucidated, especially in macrophages. One possible mechanism is a role of cell adhesion in hyperoxia-induced cell cycle arrest. To evaluate this finding, macrophages were cultured in normoxia (21% O 2 ) or hyperoxia (95% O 2 ) in adhesion or low adhesion conditions. Incubation of macrophages in hyperoxia indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
1
22
1
Order By: Relevance
“…First, few Trypan blue positive signals, an indicator for loss of membrane integrity/cell death, were detected in either RAW 264.7 cells exposed to hyperoxia or alveolar macrophages (AM) isolated from hyperoxic lungs (<5%) at a similar level as those obtained from room air controls. This finding is consistent with previous studies which indicate that exposure to hyperoxia does not decrease viability of macrophages [21,22,25,43,44]. In addition, RAW 264.7 cells, exposure to 65% O 2, could still proliferate (Fig.…”
Section: Reduced Phagocytosis Of P Aeruginosa Is Not Due To Decreasesupporting
confidence: 83%
See 1 more Smart Citation
“…First, few Trypan blue positive signals, an indicator for loss of membrane integrity/cell death, were detected in either RAW 264.7 cells exposed to hyperoxia or alveolar macrophages (AM) isolated from hyperoxic lungs (<5%) at a similar level as those obtained from room air controls. This finding is consistent with previous studies which indicate that exposure to hyperoxia does not decrease viability of macrophages [21,22,25,43,44]. In addition, RAW 264.7 cells, exposure to 65% O 2, could still proliferate (Fig.…”
Section: Reduced Phagocytosis Of P Aeruginosa Is Not Due To Decreasesupporting
confidence: 83%
“…The role of hyperoxia as a potential cause of lung cell injury has been extensively characterized in alveolar epithelial [12][13][14][15][16][17] and endothelial cells [18,19]. However, only a few studies have examined it's impact on alveolar macrophages [20][21][22][23]. Alveolar macrophages provide the first line of defense against inhaled bacterial pathogens [24] and are exposed to 13% oxygen under normal physiological conditions [22].…”
Section: Introductionmentioning
confidence: 99%
“…We found that hyperoxia did not alter the activity of protein kinase B (Akt), a transducer of multiple survival signals. In contrast, we found that hyperoxia induces sustained ERK activation (11). Previous studies have shown that ERK activity can play both a pro- (38 -40) and an anti-apoptotic role (34,35,41), depending on the cell type and context.…”
Section: Resultscontrasting
confidence: 53%
“…It is known that macrophages exposed to one type of oxidant stress, cigarette smoke, survive for prolonged periods of time in the lung (10). The prolonged life of the macrophages of smokers compared with our previous observations on the cell cycle effects of hyperoxia (hyperoxia induces macrophage cell cycle arrest accompanied by induction of p21 Cip1 and activation of the retinoblastoma protein (11)) suggests the activation of one or more survival pathways by hyperoxia. Macrophages, in vitro, survive hyperoxia for a prolonged period of time, and this is associated with sustained activation of extracellular signalregulated kinases (ERK) 1 (11).…”
mentioning
confidence: 62%
See 1 more Smart Citation